Fatal α-PVP and amphetamine poisoning during a sauna and autoerotic practices - Lunetta Philippe; Kriikku Pirkko; Tikka Julius; Ojanperä Ilkka (Springer, 2025)
We describe the sudden death of a middle-aged man while having a sauna under the influence of alpha-pyrrolidinovalerophenone (alpha-PVP) (PM blood concentration: 0.8 mg/L), amphetamine (0.34 mg/L), and other drugs (buprenorphine, benzodiazepines), and engaging in solitary sexual activities. The drugs' effects on the cardio-circulatory system and on body thermoregulation combined with the high temperatures are likely to have been central mechanisms leading to death. The high levels of adrenaline triggered by sexual arousal and the respiratory depression caused by buprenorphine, in association with benzodiazepines, may have also contributed to his death. This previously unreported type of accidental autoerotic death illustrates the risk of using amphetamine-like sympathomimetic drugs (e.g. cathinone derivates) in hot environments such as a sauna, and during sexual activities therein.